IMPLEMENTASI PEMBELAJARAN LANGSUNG MEMBUAT PAES PROPOSIONAL PADA PENGANTIN INDONESIA JOGJA - Vony F.S; Sulistiami sulis (WAHANA, 2017)
Study aims to determine the results of learning to make paes proportionally through direct learningmodel approach. The study used a one shots case study design study. The subjects of the study werestudents of Adi Buana University class of 2016, amounting to 25 people. Methods of data collectionusing written tests make design and performance tests make paes on the model. The bride Yogja Putriis one of the bridal makeup styles of court the Yogjakarta. Characteristic of the bride Java princess isa form of paes on the forehead that only uses a shoot, without using prada. Making bridal paes bothsolo and Yogja, Originally using traditional methods, but as the development of science then themethod proportional to alternative making paes. Paes is a black or green forehead makeup. Paes onthe bride Yogja consists of 4 parts, namely penunggul, penyep, penitis and godeg. The purpose of thisstudy is to know the learning outcomes of making Yogja princess paes with direct learning modelproportionally, Proportional Technique is Technique of making paes which base on visualization ofbridal face that is peak of nose and corner of eye of outside. These benchmarks are used to makepenunggul, penitis, pengapit and godeg. The purpose of making paes proportionally is to ease inmaking paes for beginners, especially students. Learning outcomes make paes proportionally easierby using visualization of the bridal face as a benchmark. This is evidenced by the increase of learningoutcomes from making the design to the actual model of the cycle I average obtained by 83.3%, thesecond cycle of 89.7%, and the average III cycle obtained 95.5%.